Pengelolaan Pariwisata Danau Napangga Berkelanjutan di Era Pandemi COVID-19 - Mayarni Mayarni; Mimin Sundari; Resa Vio Vani (Dinamika Lingkungan Indonesia, 2021)
This study aims to determine the management of Lake Napangga tourism objects in Kepenghuluan Tanjung Medan, Rokan Hilir Regency, which contributes to the economy of the surrounding community. Lake Napangga is one of the lakes located in the Rokan Hilir area which has promising tourism potential if managed properly. Therefore, the role of BUMDes as the manager of Lake Napangga should be able to become a spirit in developing this lake tourism object to empower the economy of the village community, but the management of this tourist attraction is not only influenced by the seasonal agenda but also the Coronavirus Disease pandemic that emerged in 2020 This study choosing the type of qualitative research with a case study approach, where data collection is done by observation and interviews. After the data and information are obtained, it will be analyzed in depth with triangulation techniques. The results of this study found that the management of Lake Napangga tourism objects has not run optimally by the BUMDes in this case due to the inconsistency in the number of tourists visiting Lake Napangga, the inconsistent seasonal agenda, the lack of promotional activities and the COVID-19 Pandemic that appeared regularly. Suddenly disrupting the sources of income for people who depend on this Lake Napangga tourist attraction. This reality is what makes community economic empowerment in order to increase income still not running optimally. And aspects of sustainability in this case are needed to develop the tourism potential of Lake Napangga in the face of unforeseen conditions, in this case COVID-19 becomes an example of problems that must be faced in order to run the economy of the community and maximize the management of potential tourist attractions.